2014
DOI: 10.1051/0004-6361/201424589
|View full text |Cite
|
Sign up to set email alerts
|

Formation of starspots in self-consistent global dynamo models: Polar spots on cool stars

Abstract: Context. Observations of cool stars reveal dark spot-like features on their surfaces. These starspots can be more extended than sunspots and cover a large area of the stellar surface. While sunspots appear only at low latitudes, starspots are also found in polar regions, in particular on rapidly rotating stars. Conventional flux-tube models have been invoked to explain starspot properties. However, these models use several simplifications, and so far, neither sunspots nor starspots have been generated in a sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 91 publications
(155 reference statements)
8
56
0
Order By: Relevance
“…When the helicity is large at high latitudes, i.e., when we choose the helicity profile with n = 0, magnetic spots are found to form close to the poles in a fashion reminiscent of recent simulations by Yadav et al (2015). Figure 14 presents the formation of bipolar spots near the pole for run H2.…”
Section: High-latitude Spotssupporting
confidence: 54%
See 1 more Smart Citation
“…When the helicity is large at high latitudes, i.e., when we choose the helicity profile with n = 0, magnetic spots are found to form close to the poles in a fashion reminiscent of recent simulations by Yadav et al (2015). Figure 14 presents the formation of bipolar spots near the pole for run H2.…”
Section: High-latitude Spotssupporting
confidence: 54%
“…Figure 14 presents the formation of bipolar spots near the pole for run H2. By contrast, the work of Yadav et al (2015) showed just a single spot. However, in both cases the underlying dynamo process is a distributed one, so the lower boundary at the bottom of the domain is not critical for its operation.…”
Section: High-latitude Spotsmentioning
confidence: 89%
“…Given their size and further expansion when ascending to the surface, their role in sunspot formation remains inconclusive. An alternative to producing spots in a global dynamo simulation of rapidly rotating stars was found by Yadav et al (2015). These authors were able to generate a single polar spot without the help of rising tubes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, numerical simulations of convective dynamos produce diffuse magnetic fields throughout the convection zone (e.g. Ghizaru et al 2010;Käpylä et al 2012b;Yadav et al 2015;Augustson et al 2015), which could act as the seed field for NEMPI.…”
Section: Introductionmentioning
confidence: 99%